Unexpected Severe Bocavirus Infections among Hospitalized Children during the COVID-19 Pandemic - Kara, Yalcin; Kizil, Mahmut Can; Arslanoglu, Mehmet Ozgur; Kacmaz, Ebru; Dalokay, Nidai; Pala, Ezgi; Kiral, Eylem; Bozan, Gürkan; Us, Tercan; Kiliç, Omer; Dinleyici, Ener Cagri (Journal of Pediatric Infectious Diseases, 2023)
Objective Acute respiratory tract infections are one of the leading causes of morbidity and mortality in children. Although human bocavirus (HBoV) infections are not as common as other seasonal respiratory viruses, children who are infected with HBoV are more likely to suffer from a variety of respiratory conditions, including the common cold, acute otitis media, asthma exacerbations, bronchiolitis pneumonia, some of the affected children require pediatric intensive care unit stay. Here, we aimed to evaluate pediatric bocavirus (HBoV) cases presenting with severe respiratory tract symptoms during the coronavirus disease 2019 (COVID-19) pandemic.Methods This retrospective study evaluated the medical records of children diagnosed with respiratory infections, followed up at the Faculty of Medicine, Eskisehir Osmangazi University between September 2021 and March 2022. In this study, patients with HBoV identified using nasopharyngeal polymerase chain reaction (PCR) were considered positive. Cases were analyzed retrospectively for their clinical characteristics.Results This study included 54 children (29 girls and 25 boys) with HBoV in nasopharyngeal PCR samples. The cases ranged in age from 1 month to 72 months (median 25 months). At the time of presentation, cough, fever, and respiratory distress were the most prevalent symptoms. Hyperinflation (48%), pneumonic consolidation (42%), and pneumothorax–pneumomediastinum (7%) were observed on the chest X-ray; 54% of the children required intensive care unit stay. The median length of hospitalization was 6 days. Bacterial coinfection was detected in 7 (17%) children, while HBoV and other viruses were present in 20 (37%) children; 57% of children received supplemental oxygen by mask, 24% high-flow nasal oxygen, 7% continuous positive airway pressure, and 9% invasive mechanical ventilation support. Antibiotics were given to 34 (63%) cases, and systemic steroid treatment was given to 41 (76%) cases. Chest tubes were inserted in three out of the four cases with pneumothorax–pneumomediastinum. All patients were recovered and were discharged from the hospital.Conclusion The COVID-19 pandemic changed the epidemiology of seasonal respiratory viruses and the clinical course of the diseases. Although it usually causes mild symptoms, severe respiratory symptoms can lead to life-threatening illnesses requiring intensive care admission.
Keywords: children; COVID-19 pandemic; bocavirus